Safety and efficacy of dual emission endoscopic laser treatment in patients with upper or lower gastrointestinal vascular lesions causing chronic anemia: results from the first multicenter cohort study - Tontini, Gian Eugenio; Dioscoridi, Lorenzo; Rimondi, Alessandro; Cantù, Paolo; Cavallaro, Flaminia; Giannetti, Aurora; Elli, Luca; Pastorelli, Luca; Pugliese, Francesco; Mutignani, Massimiliano; Vecchi, Maurizio (Endoscopy International Open, 2022)
Objectives and study aims Recent pilot studies have assessed the feasibility of a novel 1.9-/1.5-μm dual emission endoscopic laser treatment (1.9-/1.5-μmDEELT) for endoscopic hemostasis, ablation and resection. In this study, we investigated the safety and efficacy of 1.9-/1.5-μmDEELT in patients with chronic anemia due to gastrointestinal vascular lesions in a real-life multicenter cohort setting.Patients and methods Consecutive patients with moderate/severe iron-deficiency anemia undergoing 1.9-/1.5-μmDEELT for upper and lower gastrointestinal bleeding due to vascular lesions were enrolled in three academic referral centers. Safety and successful ablation of vascular lesions were the primary outcomes. Long-term hemoglobin level, blood transfusion requirements, endoscopic severity scores of complex vascular disorders and technical lasing parameters were also assessed. Long-term hemoglobin variations have been further assessed, with repeated measure analysis of variance and univariate analyses.Results Fifty patients (median age 74; range 47 to 91 years) with gastric antral vascular ectasia (GAVE) (22), angioectasia (22) and radiation proctopathy (6) underwent 58 1.9-/1.5-μmDEELT between 2016 and 2020. All procedures were technically feasible leading to successful ablation of the targeted lesion/s, with no incident or adverse event potentially related to the 1.9-/1.5-μmDEELT technique. Within a 6-month follow-up, hemoglobin values significantly rose (+ 1.77 at 1 month and + 1.70 g/dL at 6 months, P < 0.01), the blood supply requirement decreased (at least one transfusion in 32 versus 13 patients, P < 0.01), and GAVE lesions showed a clear endoscopic improvement (from 5 points to 1 points, P < 0.01).Conclusions The 1.9-/1.5-μm laser system is a safe and effective endoscopic tool for haemostatic ablation of bleeding vascular lesions within the gastrointestinal tract in tertiary referral centers.